Simplified Approach for Repair of Early Pseudoaneurysm of the Left Coronary Button Following Composite Graft Due to Acute Type A Aortic Dissection - Carrel, Thierry; Hurni, Samuel; Huber, Christoph; Englberger, Lars (AORTA, 2016)
We present a simplified surgical technique that was performed on a 37-year-old man who presented with a pseudoaneurysm of the left coronary ostium two months after repair of acute Type A aortic dissection with a composite graft. Intraoperatively, the surgical sites showed extreme adhesions. The leakage at the level of the coronary suture line was exposed from inside the aortic graft. Repair was performed using 7.0 polypropylene sutures, and the postoperative course was uneventful. The patient was discharged on postoperative day six without further complications.
Keywords: Aortic dissection; Composite graft; Coronary button; Pseudoaneurysm